2000
DOI: 10.1128/aac.44.5.1163-1167.2000
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Immunogenicity and Safety of a Virosome Influenza Vaccine with Those of a Subunit Influenza Vaccine in Pediatric Patients with Cystic Fibrosis

Abstract: The objective of this study was to compare the immunogenicity and safety of a single-dose regimen and a two-dose regimen of a trivalent virosome influenza vaccine (Inflexal Berna V) with those of a trivalent subunit influenza vaccine (Influvac) in children and adolescents with cystic fibrosis (CF). In an open, randomized, multicenter study with parallel groups, 11 young children with CF (1 to 6 years old) and 53 older children and adolescents with CF (>6 years old) were randomly assigned to one of the followin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0
2

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(37 citation statements)
references
References 24 publications
1
34
0
2
Order By: Relevance
“…In our cohort of participants, 64% (107/168) experienced and reported at least one solicited AEFI in the first week following vaccination, which is similar to proportions reported after IIV: 15/ 21 (71%) participants with CF vaccinated with IIV reported at least one systemic AEFI in the 5 days following vaccination [41]. Fiftynine (35%) patients had onset of fever during the first six days following vaccination with most febrile children observed on day 4 post-vaccination (n = 42, 25%).…”
Section: Laiv In Subjects With Cf: Safety and Immunogenicitysupporting
confidence: 85%
“…In our cohort of participants, 64% (107/168) experienced and reported at least one solicited AEFI in the first week following vaccination, which is similar to proportions reported after IIV: 15/ 21 (71%) participants with CF vaccinated with IIV reported at least one systemic AEFI in the 5 days following vaccination [41]. Fiftynine (35%) patients had onset of fever during the first six days following vaccination with most febrile children observed on day 4 post-vaccination (n = 42, 25%).…”
Section: Laiv In Subjects With Cf: Safety and Immunogenicitysupporting
confidence: 85%
“…The immunogenic effect of influenza vaccines in CF children is comparable to that of healthy individuals [67] and several studies have demonstrated the safety of influenza vaccinations in children with CF [68]. One study has compared a virosome adjuvant vaccine with a subunit vaccine in paediatric CF patients detailing their strong efficacy and tolerability [69]. The coming live attenuated intranasal vaccines will offer an alternative more suitable for children and reduce the number of injections.…”
Section: Influenzamentioning
confidence: 97%
“…Recently, a virosomal-adjuvanted subunit influenza vaccine was shown to be well tolerated and endowed with improved immunogenicity. [36][37][38][39][40] To evaluate the amplitude and duration of the cellmediated and humoral immune responses elicited by such vaccine preparation in pediatric HIV infection, we designed a study protocol enrolling HIV-infected children in whom long-term HAART resulted in an optimal immunovirologic response to therapy.…”
mentioning
confidence: 99%